Les Transparences - Lorraine Alexandre (Glad!)
This text presents my series of performative photographs called Les Transparences (“Transparencies”), 2007. By staging drag queens models, this series brings face-to-face the biological nature of sex and the performative nature of genders. Thereby I question the arbitrary value of associating sex and gender while observing the sociocultural laws that regulate it. In my artistic practice, I use masks and stereotyped body postures as visual discourses that make the body into a screen on which a culturally recognisable identity is displayed. I question the relationship between art and life. My portraits never show individuals but rather performing and performative bodies that both carry discourses on identity and claim identities through an artistic staging.